O ensino remoto de ‘lutas no mundo’ em aulas de educação física na pandemia de covid-19 - Colloca, Pedro Maiorano (Universidade Federal de São Carlos, 2021)
During the covid-19 pandemic, many sectors of civil society were harmed in all different ways. The school was one of the institutions that felt intensely the impacts of this phenomenon, starting by its closure, which opened up, in a way never seen before, the inequalities of our educational system. With regard to the pedagogical scope, even though it is still not clear what the real impacts of all this time without face-to-face activities at school are, it is important to think about what strategies are being successfully applied by teachers, considering that understanding this scenario is a way of listing new teaching practices that can be adopted in remote education. With this in mind, this work seeks to understand how school physical education rethought the teaching of the thematic unit 'fights in the world', taking into account that this content supposedly requires direct contact between the participants in order to be learned. Considering that the main goal of this research was to analyze a didactic unit for teaching fights, built in a collaborative way, with the Physical Education teacher from the state school system in the state of São Paulo. In order to carry it out qualitatively, I chose as data collection instruments a semi-structured interview with a teacher at the school, a questionnaire sent to the students in a ninth grade class, and finally, comments on a classroom's facebook group, created by the school's coordination. Data were analyzed, reaching the following categories. a) Being a teacher in the pandemic, encompassing my reflections on the understanding that the interviewed teacher has about this process; b) Planning of physical education classes during the pandemic, in which I was able to point out how the curriculum influenced the organization of the teaching unit during this pandemic moment; and, c) If the fights arouse interest, whoever fights does not fight either, in which I evidenced the students' understanding of the didactic unit worked on. As final considerations, I could infer that being a teacher in the pandemic is not a simple task, requiring an apparently more urgent effort to reflect on pedagogical practice. In addition, the fact that the Currículo Paulista was designed for face-to-face teaching and had been applied online was an imperative for the way we conduct the class planning. Finally, I understood that the students had good use of the didactic unit, considering the rather elaborate understanding of the 'world struggles' they had, in addition to the autonomy they had to build their own meanings in relation to the theme, which was expressed, respectively, on the Facebook rating and comments.
Remote teaching of 'fights around the world' in physical education classes in the covid-19 pandemic
Keywords: Educação física escolar; Ensino das lutas; Covid-19; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM